Analisis Dokumentasi atas Sistem Pengendalian Interal, Manajemen Risiko, dan Kompetensi Auditor terhadap Efektivitas Prosedur Audit - Revanya Adinda Putri; Nera Marinda Machdar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the influence of the internal control system, risk management, and auditor competency on the effectiveness of audit procedures, as well as assessing how the auditor's experience acts as a moderating variable in this relationship. The results of previous research show that the internal control system, risk management and auditor competency have a positive effect on audit effectiveness, however several studies provide varied results regarding the role of auditor experience. The contribution of this research strengthens the literature regarding risk-based auditing and the quality of audit procedures in modern corporate governance.